Post-Disaster Recovery Efforts for Enhancing Student Health, Physical Fitness, and Safety in Aceh, Indonesia - Aghus Sifaq; Dessy Rindiyanti Harista; Shery Iris Zalillah (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2026)
In 2025, Aceh experienced a flood disaster that resulted in the loss of homes in several areas. A total of 203 sub-districts were affected by the disaster, approximately 2 million people were impacted, and around 111 thousand people were displaced according to data from the Aceh Provincial BPBD as of January 16, 2026. During the recovery period after the flood disaster, elementary school students face various problems, such as declining health conditions due to an unhygienic environment, reduced physical activity leading to decreased fitness, and an increased risk of accidents and injuries in the school environment. Therefore, a structured and sustainable school-based community service program is needed thru an integrated educational approach that incorporates health, fitness, and safety aspects for elementary school students after the flood disaster. The implementation of this community service activity is carried out by developing an appropriate curriculum for students in emergency schools during the post-disaster recovery period.